ANALISIS KEMISKINAN DENGAN PENDEKATAN MODEL REGRESI SPASIAL DURBIN (Studi Kasus: Kabupaten Gianyar) - PRATIWI, LUH PUTU SAFITRI; SRINADI, I GUSTI AYU MADE; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 2 No 3 (2013)DO - 10.24843/MTK.2013.v02.i03.p042, 2013)
Poverty still a complex problems for both at national and regional level, so it requires an appropriate and sustainable strategy mitigation. Every household in the different regions has different characteristics and influenced factors, so it requires the identification of the factors that influence poverty by paying attention to the influence of the area using the Spatial Durbin Model (SDM). The purpose of SDM modeling is to determine the spatial dependency relationship which occur not only in the dependent variables, but also on the independent variables. The result shows that the significant lagged dependent variable is indicated by the p arameter Lag significant independent variables are independent variables with a significant weighting, but there are no independent variables that are significant with the weighting.
Keywords: Poverty, OLS, Spatial Durbin Model